"Study of Sadr al-Muta'allehin's citation to Ghazali on the issue of true monotheism" - Seyedeh zahra Mousavi baygi; Hooran Akbarzadeh (حکمت اسرا, 2021)
Monotheism is one of the most important issues addressed by scholars of different Islamic sects and schools. Although in most of these schools, monotheism is a multifaceted truth, there are different views about the highest level of monotheism. This research, which has been written in an analytical-descriptive method, tries to compare and evaluate the true monotheism or the monotheism of the people of knowledge in their views after interpreting and analyzing the true monotheism from the perspective of Mulla Sadra and Ghazali. The result obtained from the studies is that despite the apparent similarities in the expressions of Mulla Sadra and Ghazali as well as the numerous references of the mullah to him in matters related to personal unity of existence, monotheism has different faces for these two thinkers. Mulla Sadra, in his final view, believes in the unity of existence, but al-Ghazali's view on this is not clear. However, the evidence is more based on the fact that from al-Ghazali's point of view, monotheism is the unity of intuition. Based on this difference, the reason for Mulla Sadra's numerous citations to Ghazali in the discussions of monotheism should either be due to Mulla Sadra's lack of attention to the difference between the unity of existence and the unity of intuition, or Sadr al-Muta'allehin's shrewdness in persuading the enemy